Review of competency-based models and quality standards in training and education in the addiction field: Study protocol - Nováková, Elizabeth; Volfová, Anna; Lososová, Amalie; Svěcená, Kateřina; Miovský, Michal (Adiktologie, 2023)
There is a growing trend of development and improvement of education and training in the field of addictions, hand in hand with the increase and changes of substance use-related issues. To ensure a high level of education quality it is necessary to name and define competency-based models and quality standards of different groups of addiction workforce/professionals in various drug demand reduction settings (prevention, treatment/ social reintegration/recovery, and harm reduction) as it is important to guarantee high-quality care to the target group of people dealing with substance use issues and addiction (including behavioural addictions). METHODS: The aim of the study is to identify quality standards and competency-based models in education programmes and training for addiction professionals/workforce. A review of available literature sources focusing on quality standards and competency-based models in training and education in the addiction field is going to be conducted. We will search for any eligible articles from selected electronic databases (e.g., PubMed, EBSCO, Scopus), grey literature, and the internet. The Preferred Reporting Items for Systematic reviews and Meta- Analysis (PRISMA) will be followed for study selection and reporting. Titles and abstracts will be independently reviewed for relevance and full-text studies acquired for analysis. The documents found will be kept in a single file, added to and sorted, and analysed for the types of standards, curricula, and training modules that exist, with a focus on identifying competencies. ETHICS AND DISSEMINATION: This study does not include human participants or other subjects requiring ethical approval. The research project is going to be implemented in accordance with ethical standards. The results will be published in a professional journal and presented at the Lisbon Addiction Conference 2024. The next steps would lead to open discussions with relevant stakeholders.